Risk-benefit Analysis of Antidepressants Use during Breastfeeding to Treat Postpartum Depression - Vânia, Leal; Paula, Fonseca, Ana (Medical Science: Recent Advances and Applications Vol. 5, 2025)
Postpartum depression is classified as a major depressive disorder, and the causes are not well known. Postpartum depression affects approximately 14.5% of women, and it can affect both mother and infant. Therefore, rapid attention and treatment are imperative. The causes of postpartum depression are not well known; but there are many factors that may increase the risk of developing the disease. Women should be carefully evaluated after childbirth for depressive or anxiety symptoms with adequate screening tools and methods to avoid diagnostic errors; especially when dealing with women who present risk factors. The pharmacological approach often represents one of the most realistic options for treatment. However, women may be reluctant to take antidepressants because of the fear of adverse effects on the infant, since most drugs pass into breast milk. The objective of this review is to evaluate the risk-benefit of using antidepressants during breastfeeding to treat postpartum depression. An electronic search was performed by using the PubMed database from January 2001 through December 2010. The search was limited to articles in the English language and to articles that relate to human research. Manual searches of bibliographies were also conducted to identify additional pertinent studies. The use of antidepressants that do not appear in infants’ plasma, for which use during breastfeeding is better documented and at standard therapeutic doses is recommended, such as sertraline and paroxetine. Fluoxetine has a long half-life, which can lead to a long infant exposure through breast milk, and citalopram can cause adverse effects in infants exposed through breast milk. Therefore, citalopram and fluoxetine should not be used as first-line treatments. If these drugs are used by a nurse, they should take the lowest effective dosage, and their infants should be monitored. This study focused on emphasising the importance of postpartum depression treatment, always considering its repercussions for the breastfed infants. Studies are needed with larger samples to properly evaluate the short and long-term effects of antidepressants on infants exposed through breast milk, so that clinicians can create standard decisions regarding the treatment of postpartum depression, without putting infants at risk.